An Investigation into Linguistic Deviation in the Students’ Translation of “The Road Not Taken” by Robert Frost - Supeno Supeno (Journal of English Language Studies, 2019)
Poetic diction has its own characteristic features and anyone engaged in translation of a poem should have a sufficient understanding. According to Leech (1969), what causes linguistic deviation in translating poetry is that the poet manipulates the general language rules in his poem as a means of creating artistic beauty. Since the form and the meaning in a poem are inseparable, a translator of a poem should do his best to transfer these two aspects as otherwise he/she produces some linguistic deviations in the translation. So far little attention has been paid to linguistic deviations in translation of English poems. This study is intended to investigate such matter by analyzing the linguistic deviations in the translations of the poem “The Road Not Taken” by Robert Frost. Ten students of sixth semester of English Education Department of Universitas Wijaya Kusuma Surabaya (UWKS) participated in the study. The result of the analysis showed that although the students have passed two obligatory subjects exams, Vocabulary and Structure, both lexical and grammatical deviations are still two most dominant compared to other aspects. Findings also suggest that the subject of Translation should be more intensified and include literary texts in its weekly meetings.